2019
DOI: 10.25103/ijbesar.122.04
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotional Intelligence on Organizational Performance Among Insurance Companies in Kenya

Abstract: Positivism research philosophy was adopted for the study. Descriptive and explanatory cross-sectional research designs were used. The target population consisted of all the 55 registered insurance companies in Kenya as at 28th February 2017 and a sample size of 208 participants drawn from lower, middle and top level. Primary data was collected using collected using semi-structured questionnaires containing both open and closed-ended questions while secondary data was obtained using a secondary data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The guidance and support from experienced colleagues helped employees overcome work-related challenges and achieve better performance. Similarly, the findings of the current research align with the study by Wangari et al (2019), which found that relationship management (social skills) significantly predict work performance of employees who worked in insurance firms in Kenya. The ability to effectively manage relationships and interactions with colleagues positively impacted the employees' overall job performance.…”
Section: Discussionsupporting
confidence: 89%
“…The guidance and support from experienced colleagues helped employees overcome work-related challenges and achieve better performance. Similarly, the findings of the current research align with the study by Wangari et al (2019), which found that relationship management (social skills) significantly predict work performance of employees who worked in insurance firms in Kenya. The ability to effectively manage relationships and interactions with colleagues positively impacted the employees' overall job performance.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the model is statistically significant in predicting the relationship between self-leadership and organizational performance. With regard to emotional intelligence as a dimension of self-leadership, this study supports both Agarwal and Singh (2020) in UAE and Wangari et al (2019) in Kenya who found that emotional intelligence significantly affects performance. The study findings align with Zia-ur-Rehman and Zia (2020) who found that emotional intelligence competencies had a significant impact on corporate leadership and ultimately organizational performance.…”
Section: Regression Anova For Self-leadershipsupporting
confidence: 74%
“…Emotional intelligence comprises aspects of self-awareness and self-management which relate to one's personal competence, while social awareness and relationship management are associated with external competence (Xavier, 2005). Agarwal and Singh (2020) and Wangari, Gichuhi and Macharia (2019) found a significant relationship between emotional intelligence through its dimensions of self-awareness, self-management, social awareness, relationship management and organizational performance. Wong and Law (2002) note that social interactions require emotional awareness and emotional regulation.…”
Section: Emotional Intelligencementioning
confidence: 98%